Comparison of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/MRI in the Preoperative Diagnosis of Gastric Cancer - Tao Du; Shun Zhang; Xi-Mao Cui; Ren-Hao Hu; Hai-Yan Wang; Jian-Juan Jiang; Jun Zhao; Lan Zhong; Xiao-Hua Jiang (Canadian Journal of Gastroenterology and Hepatology)
Purpose. Our objective was to compare the value of positron emission tomography/magnetic resonance imaging (PET/MRI) with the new imaging agent [68Ga]Ga-DOTA-FAPI-04 and the traditional imaging agent [18F]FDG for the preoperative diagnosis of gastric cancer. Methods. Forty patients with gastric cancer diagnosed by gastroscopy in gastrointestinal surgery at our hospital from June 2020 to January 2021 were analyzed. All patients underwent simultaneous [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/MRI. The standard uptake value (SUV), fat removal standard uptake value (SUL), and diagnostic sensitivity, specificity, and accuracy for primary and metastatic lesions were compared, and their diagnostic value for different lymph node dissection stages was analyzed. Results. The median age of the patients in this cohort was 68 years. Twenty-nine patients underwent surgery, and 11 patients underwent gastroscopic biopsy. The SUVmax of primary lesions in the FDG group and the FAPI group was 5.74 ± 5.09 and 8.06 ± 4.88, respectively (P<0.01); SULmax values were 3.52 ± 2.80 and 5.64 ± 3.25, respectively (P<0.01). The SUVmax of metastases in the two groups was 3.81 ± 3.08 and 5.17 ± 2.80, respectively (P<0.05). The diagnostic sensitivities for primary lesions in the FDG group and the FAPI group were 0.72 and 0.94, respectively (P<0.05). Combined with postoperative pathological staging, there was no difference in diagnostic sensitivity and specificity of lymph node staging between the FDG and FAPI groups (P>0.05). Conclusion. Compared with the traditional imaging agent, [68Ga]Ga-DOTA-FAPI-04 has better diagnostic efficiency but no substantial advantage for preoperative lymph node staging.